A new species of the Eleutherodactylus lacrimosus assemblage (Anura, Brachycephalidae) from the lowland rainforest canopy of Yasuni National Park, Amazonian Ecuador - McCracken, Shawn F.; Forstner, Michael R. J.; Dixon, James R. (Phyllomedusa: Journal of Herpetology, 2007)
A new species of Eleutherodactylus from the lowland rainforest canopy in northeastern Amazonian Ecuador is described. It is placed in the Eleutherodactylus lacrimosus assemblage of the greater unistrigatus group. It is most similar to the sympatric species Eleutherodactylus lacrimosus, but differs by the lack of a papilla at the tip of the snout, tubercles on upper eyelids, tubercles on dorsum, dorsal markings, and larger body size, and the presence of lateral fringes on the fingers and a tarsal fold. The new species inhabits tank bromeliads in the upper strata of the rainforest canopy at heights of 23.5-38.0 m. The effects of implementation of canopy surveys on biological diversity are briefly discussed.